A New Concept of Managing Tourist Region - Fedyk, Wojciech; Meyer, Beata; Potocki, Jerzy (Studia Oeconomica Posnaniensia, 2017)
The article contains the results of an analysis concerning the possibilities of effectively managing tourist regions in a competitive market, on the basis of the functioning of regional tourist organizations (ROT) in Poland according to several models. Furthermore, the results of the proposed ROT transformations and their influence on the development of tourist traffic in tourist reception areas are discussed. A literature review showcased the divergence of views on the purposefulness and direction of the POT-ROT-LOT system modifications. Three models of ROT activity were proposed on the basis of the idea of product consortia and tourism clusters, DMO and network cooperation, indicating the key qualities that allow for the implementation of those models in organizational practice. As a consequence, these qualities contribute to increasing the organizations' effectiveness, and further implicate changes in logistics and the quality of tourist service in tourist regions.